STRATEGI PENGEMBANGAN LEMBAGA PENDIDIKAN KEJURUAN (LPK)DI MASYARAKAT - Yoyon Suryono (Jurnal Cakrawala Pendidikan, 2007)
Secondary school graduates need vocational training institutionsbecauseof the socioeconomic benefits they will get after graduatingfrom the institutions. They will get more benefits from theinstitutionsif the management of the institutions is decentralisticallyimproved. The aimof a research this article is about was identifyingthe need to improve the vocational training institutions which aredecentralistically managed. The resultof the research can be used todetermine a strategy to develop and to certify vocational traininginstitutions. The resultofthe research shows that vocational traininginstitutions, even with the decreasing numbersof their students, arestill needed by society. These institutions also give benefits as unitsof non-formal education offering various training programs.Although generally their organization is small in scale, theirautonomy is great. The efficiency and effectivenessof their use ofthe infrastructure is good. Some of the institutions are tied to thenational curriculum, their license to operate, the nationalexamination, graduation standards, and certifications.To developthe institutions, wider authority is needed to manage the institutionsdecentralistically, particularly in relation to aspectsof programdevelopment, the curriculum, their license, the national examination,graduate standards, and their authority to issue certificates based onthe accreditationof the institutions. In order to implement suchdevelopment, a strategyof development and certification as a formof infrastructure investment and program development is needed.They cango through their development and certification well byproviding representative buildings, educational programs which are 'sold OUt', and professional management employing qualitymanagemen